Successful Management of Sequential Pulmonary Infections in a Cardiac Transplant Recipient - John Galbraith; Jutta K Preiksaitis; Sandra Czekanski; Mark J Poznansky; Mohamed Hirji (Canadian Journal of Infectious Diseases)
A case of a cardiac allograft recipient who had an initial combined pulmonary infection with cytomegalovirus, Aspergillus fumigatus and Nocardia asteroides, successfully treated with liposomal amphotericin B and sulfisoxazole and followed by an episode of respiratory syncytial virus pneumonitis, is presented. This case illustrates the role of computed tomographic imaging in the recognition, diagnosis and monitoring of complex opportunistic pulmonary infections and the benefits of liposomal amphotericin B in the treatment of aspergillosis.